Population dynamics and seasonal variation in biological characteristics of black sea bream (Acanthopagrus schlegelii) in Zhanjiang coastal waters, China - Lauden, Hagai Nsobi; Lyu, Shaoliang; Alfatat, Alma; Mwemi, Happiness Moses; Alam, Jamaluddin Fitrah; Chen, Ning; Wang, Xuefeng (Frontiers in Marine Science, 2025)
This study examined the population dynamics and seasonal variation (winter-summer) in the biological characteristics of black sea bream (Acanthopagrus schlegelii) in Zhanjiang coastal waters, China. Key growth parameters were estimated using the von Bertalanffy growth model, revealing an asymptotic length (L∞) of 505.05 mm and a growth coefficient (K) of 0.26 year-¹, with an estimated longevity of 11.24 years. Mortality analysis showed a total mortality rate (Z) of 0.35 year-¹, primarily driven by natural causes (M = 0.33 year-¹) with minimal fishing impact (F = 0.02 year-¹), resulting in a low exploitation rate (E) of 0.05. Length-weight relationship (LWR) analysis indicated positive allometric growth in females and nearly isometric growth in males, with significant seasonal variations in condition factors (K). Yield Per Recruit (YPR) analysis identified a maximum sustainable exploitation rate (Emax) of 0.421, with a conservative management approach suggested at E0.1 = 0.355. Seasonal variations in reproductive indices, with higher Gonadosomatic Index (GSI) and Hepatosomatic Index (HSI) in winter, highlight the species’ reproductive cycle. The findings suggest that Acanthopagrus schlegelii is stable, with low fishing pressure. Seasonal GSI and HSI variations suggest fisheries management should time fishing to reduce impacts on reproductive success. Maintaining exploitation rates below Emax is essential for sustainable management, contributing valuable insights for fisheries conservation in coastal China.